2013
DOI: 10.1038/hdy.2013.99
|View full text |Cite
|
Sign up to set email alerts
|

Estimating genome-wide heterozygosity: effects of demographic history and marker type

Abstract: Heterozygosity-fitness correlations (HFCs) are often used to link individual genetic variation to differences in fitness. However, most studies examining HFCs find weak or no correlations. Here, we derive broad theoretical predictions about how many loci are needed to adequately measure genomic heterozygosity assuming different levels of identity disequilibrium (ID), a proxy for inbreeding. We then evaluate the expected ability to detect HFCs using an empirical data set of 200 microsatellites and 412 single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(141 citation statements)
references
References 40 publications
12
128
1
Order By: Relevance
“…95% quantiles crossed zero) [all markers: r HHC = -0.06, 95% CI = -0.068-0.196; g 2 = 0.001, 95% CI = 0.002-0.006, P = 0.17]. The expected power to detect HFCs according to Miller et al (2014) was small (r 2 = 0.06). Parental heterozygosity was not significantly associated with offspring heterozygosity (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…95% quantiles crossed zero) [all markers: r HHC = -0.06, 95% CI = -0.068-0.196; g 2 = 0.001, 95% CI = 0.002-0.006, P = 0.17]. The expected power to detect HFCs according to Miller et al (2014) was small (r 2 = 0.06). Parental heterozygosity was not significantly associated with offspring heterozygosity (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We did not detect positive heterozygosity-heterozygosity correlations (HHCs; Balloux et al 2004) for our microsatellite markers set, also the parameter g 2 gave no indication for inbreeding in our population, giving no support to the general effect hypothesis. However, according to formulae from Miller et al (2014) the power of our markers to estimate inbreeding in our study system was rather small. It must be kept in mind that the nonsignificant values should not be misinterpreted as disproving general effects, as the effects of weak inbreeding are more readily detected on the phenotypic level than on the level of a limited number of markers (Szulkin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As ID is considered a definite consequence of inbreeding and the proximal cause of HFCs, in the absence of ID (if g 2 ¼ 0), HFCs are not expected to arise [13]. Indeed, following the formula proposed by Miller et al [81], when g 2 ¼ 0, the power to detect HFCs also becomes 0. However, other studies found HFCs despite having no evidence for ID [10,82].…”
Section: Discussionmentioning
confidence: 99%
“…(2009) have suggested that the use of fitness‐correlated traits that are only weakly influenced by inbreeding may also hamper detection of HFCs, as might the varied demographic history of populations under study (see also Canal, Serrano, & Potti, 2014; Miller et al. 2014). Further, using a small number of loci to calculate heterozygosity may fail to represent heterozygosity across the genome, which is a critical assumption of the inbreeding interpretation of HFCs (Miller & Coltman, 2014; but see Brommer, Kekkonen, & Wikstrom, 2015).…”
Section: Introductionmentioning
confidence: 99%